A core-shell catalyst for short-chain alkane hydroaromatization to aromatics and a preparation method and application thereof
Patent Information
- Application Number
- CN202611036033.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-20
AI Technical Summary
然而,现有催化体系普遍缺乏对异构化与芳构化反应路径的有效调控,难以充分发挥异构烷烃作为关键中间体的促进作用,仍然存在芳烃收率低、深度裂化严重以及催化剂稳定性不足等问题
本发明摒弃传统单一催化剂直接芳构化的反应路线,采用核壳结构双功能催化剂制备航空燃料芳烃组分。通过核壳型催化剂壳层异构化-脱氢、内核芳构化的功能分区设计,实现C3-C8轻质直链烷烃→异构烷烃及低碳烯烃→芳烃的接力转化,提高了芳烃收率,为可持续航空燃料(SAF)芳烃组分的高效制备提供了一种新的技术路线。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst preparation technology, specifically to a core-shell catalyst for the hydrogenation aromatization of short-chain alkanes to produce aromatics, its preparation method, and its application. Background Technology
[0002] Aromatics are a key blending component of Sustainable Aviation Fuel (SAF), playing a crucial role in increasing fuel density, improving the swelling performance of rubber seals, and meeting aviation fuel standards. With the global aviation industry's push for low-carbon development and the advancement of "dual-carbon" goals, developing efficient and green aromatics production technologies has become an important research direction in the field of sustainable aviation fuels.
[0003] Currently, continuous reforming catalytic technology for petroleum fractions is relatively mature, enabling efficient conversion of petroleum-based short-chain alkanes to aromatic components. However, bio-based short-chain alkanes differ significantly from petroleum-based feedstocks. Bio-based short-chain alkanes are almost entirely composed of n-alkanes, while petroleum-based feedstocks typically contain a certain proportion of isoalkanes and cycloalkanes, components more prone to aromatization. Compared to isoalkanes, n-alkanes have a more stable molecular configuration, requiring higher activation energies for cyclization and aromatization reactions. They are also more susceptible to side reactions such as deep cracking and coking during the reaction, leading to lower aromatic yields and faster catalyst deactivation. Therefore, traditional continuous reforming catalysts struggle to meet the demands for efficient aromatization of bio-based n-alkanes. Thus, if efficient conversion of n-alkanes to isoalkanes can be achieved prior to the aromatization reaction, followed by further cyclization and aromatization, it is expected to significantly improve the aromatic yield and catalyst stability of bio-based short-chain alkanes. However, existing catalytic systems generally lack effective control over isomerization and aromatization reaction pathways, making it difficult to fully leverage the promoting role of isoalkanes as key intermediates. Problems such as low aromatic yields, severe deep cracking, and insufficient catalyst stability still exist.
[0004] Therefore, developing a spatially functionalized catalyst capable of preferential isomerization of n-alkanes followed by efficient aromatization is of great significance for improving the aromatization efficiency of bio-based short-chain alkanes, increasing aromatic yields, and enhancing catalyst stability. Summary of the Invention
[0005] Based on previous research and existing problems, this invention proposes a core-shell catalyst for the hydrogenation aromatization of short-chain alkanes to produce aromatics, its preparation method, and its application. The catalyst core and shell are prepared separately by an equal-volume impregnation method, and then the shell material is uniformly coated onto the core by ball rolling to obtain the finished catalyst.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A catalyst for the aromatization of short-chain alkanes to synthesize aromatics, wherein the catalyst has a core-shell structure, the core is an aromatization functional catalytic phase, and the outer shell is uniformly coated on the outer surface of the core and is an isomerization-dehydrogenation bifunctional catalytic phase. The raw materials diffuse from the shell to the core, and the isomerization dehydrogenation and cyclization aromatization relay reactions are completed sequentially within a single catalyst particle. The kernel particle size is 0.5–4 mm, the shell thickness is 0.5–4 mm, and the kernel particle size is greater than or equal to the shell thickness.
[0007] Preferably, the core aromatization functional catalytic phase is prepared by loading an aromatization active metal component onto an aromatization molecular sieve support. The aromatization active metal is selected from at least one of Group VIII, IIB, IIIA metal elements, oxides, or metal precursor salts, and the aromatization molecular sieve support is selected from at least one of aluminosilicate molecular sieves and pure silica molecular sieves. The shell isomerization-dehydrogenation catalytic phase is prepared by co-loading the isomerization dehydrogenation active component and the promoter onto a shape-selective isomerization molecular sieve support; the shape-selective isomerization molecular sieve support is selected from at least one of ZSM-22, ZSM-48, and SAPO-11; the isomerization dehydrogenation active component is selected from at least one of Group VIII metal elements, oxides, or metal precursor salts; the promoter is selected from at least one of Group VIB and IVA metal oxides or their metal precursor salts.
[0008] Preferably, the core aromatization active metal is at least one of Ni, Zn, and Ga, and the mass fraction of the aromatization active metal in the total mass of the core is 1% to 4% based on the mass of the elemental metal; the metal dispersion of the aromatization active metal on the surface of the aromatization molecular sieve support is greater than 15%. The aromatized molecular sieve support is at least one of HY molecular sieve, MCM-22 molecular sieve, and ZSM-5 molecular sieve.
[0009] Preferably, the shell isomerization dehydrogenation active component is selected from one or more of Ni, Pt, and Pd, and the mass fraction of the isomerization dehydrogenation active component in the total mass of the shell is 0.1% to 2% based on the mass of the metal element. The shell additives are oxides or metal precursors corresponding to Cr, Mo, W, and Sn; the mass fraction of the additives in the total mass of the shell is 1% to 10% based on the mass of the metal oxides.
[0010] This invention also proposes a method for preparing a core-shell catalyst for the hydrogenation aromatization of short-chain alkanes to aromatics as mentioned above, comprising the following steps: S1. Preparation of aromatized core particles: The aromatized metal precursor salt solution was impregnated onto the aromatized molecular sieve support by an equal-volume impregnation method for 12–64 h at room temperature; the impregnated product was dried at 100–160 °C for 4–12 h and calcined at 400–600 °C for 4–12 h, and then ground to obtain core powder; a binder was added to the core powder and rolled to form core particles with a particle size of 0.5–4 mm. S2. Preparation of shell-coated powder: Shape-selective isomeric molecular sieves are dispersed in deionized water to prepare a suspension. Under constant temperature of 70-85℃ and stirring speed ≥100rpm, a mixed solution of isomeric dehydrogenation metal precursor and auxiliary precursor is added dropwise. After the addition is completed, stirring is continued for 15-20h. After standing for 4-8h, the solid is filtered and washed. The solid is dried at 100-160℃ for 4-12h and calcined at 400-600℃ for 4-12h, and then ground to obtain shell powder. S3. Rolling and Coating Molding and Post-processing: The core spheres obtained in step S1 and the shell powder obtained in step S2 are fed into a sphere forming device, and the binder is sprayed in by atomization. The spheres are rolled to uniformly coat the surface of the core, and the shell thickness is controlled to be 0.5-4 mm. The coated product is dried at 100-160℃ for 4-12 h and calcined at 400-600℃ for 4-12 h. Finally, it is reduced at 350℃ for 3 h in a hydrogen atmosphere to obtain a core-shell bifunctional catalyst.
[0011] Preferably, in step S3, during the ball forming process, the rotation speed of the ball forming equipment is controlled at 20-80 r / min.
[0012] Preferably, the binder consists of 20 wt% aluminum sol and 1.0 mol·L⁻¹ -1 The nitric acid aqueous solution is prepared at a volume ratio of 15:1.
[0013] In addition, the present invention also proposes the application of the catalyst mentioned above in the synthesis of aromatics by hydrogenation aromatization. Using C3-C8 normal light alkanes as reactants, the reaction is carried out in a hydrogenation fixed-bed reactor. The reactants first undergo isomerization and dehydrogenation reactions in the catalyst shell to generate isoalkanes and low-carbon olefin intermediates. The intermediates diffuse inward to the catalyst core to undergo cyclization aromatization reactions to generate aromatics.
[0014] Preferably, the reaction conditions are: reaction pressure 0.1~1 MPa, reaction temperature 480~550 ℃, and volume hourly space velocity 0.5~2 h⁻¹. -1 The volume ratio of hydrogen to raw materials is 10:1 to 200:1.
[0015] Preferably, the reaction raw materials are one or more mixtures of C3-C8 light alkanes.
[0016] Compared with existing technologies, this invention provides a core-shell catalyst for preparing a short-chain alkane to aromatic hydrocarbons via hydrogenation as mentioned above, its preparation method, and its application, which have the following beneficial effects: This invention abandons the traditional reaction route of direct aromatization using a single catalyst and instead employs a core-shell bifunctional catalyst to prepare aromatic components for aviation fuel. Through the functional partitioning design of the core-shell catalyst—shell isomerization-dehydrogenation and core aromatization—a relay conversion from C3-C8 light straight-chain alkanes to isoalkanes and low-carbon olefins to aromatics is achieved, improving the aromatic yield and providing a new technical route for the efficient preparation of aromatic components for sustainable aviation fuel (SAF).
[0017] The catalyst of this invention features precise matching and synergistic effects between its core and shell active components, resulting in exceptionally high catalytic activity and selectivity for target products. Under optimized reaction conditions, the conversion rate of n-hexane can stably reach over 96.0 wt%, the aromatic yield can reach a maximum of 55.6 wt%, the conversion rate of bio-light oil reaches 99.7%, and the aromatic yield is 61.3 wt%, significantly superior to traditional single-function catalysts or mixed catalytic systems, effectively improving the aromatic yield.
[0018] By constructing a core-shell spatial partitioning structure, the isomerization-dehydrogenation functional active center is spatially separated from the aromatization functional active center. This enables n-alkanes to preferentially undergo isomerization and dehydrogenation reactions in the shell, generating key intermediates such as branched alkanes and alkenes that are more prone to aromatization reactions. These intermediates then diffuse further into the core for cyclization and aromatization reactions. This design fully utilizes the higher reactivity and better aromatization efficiency of isomers compared to n-alkanes, overcoming the limitation of low direct aromatization efficiency of traditional aromatization catalysts for bio-based n-alkanes. It significantly improves the aromatization efficiency and aromatic yield of bio-based short-chain n-alkanes.
[0019] Isomerization, dehydrogenation, and aromatization reactions, which originally required segmented loading or synergistic use of multifunctional catalysts, can now be completed within a single core-shell structure catalyst. This significantly simplifies the catalytic system and improves the synergistic efficiency between different functional active sites. Simultaneously, the intermediate product transport pathway is shorter, the reaction process is more easily controlled, side reactions are effectively reduced, aromatic yields and catalyst stability are improved, and the feasibility and economics of industrial applications are significantly enhanced. Attached Figure Description
[0020] Figure 1 The present invention discloses the core-shell catalyst structure and reaction pathway diagram for the aromatization of n-hexane into aromatic hydrocarbons under hydrogen conditions. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1 100g of MCM-22 molecular sieve and 9.93g of nickel nitrate hexahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-1 was obtained by grinding.
[0023] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-1.
[0024] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-1 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. Pellet particles then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-1, which rolled into shape under the action of the atomized binder. The average core particle size was controlled to be 2 mm, and the average shell thickness to be 1 mm. The powder was dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-1.
[0025] Example 2 100g of MCM-22 molecular sieve and 9.10g of zinc nitrate hexahydrate were weighed to prepare an impregnation solution. The active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, the carrier was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-2 was obtained by grinding.
[0026] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-2.
[0027] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-2 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. Pellet particles then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-2, which rolled into shape under the action of the atomized binder. The average core layer particle size was 2 mm, and the average shell layer thickness was controlled to be 1 mm. The powder was dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-2.
[0028] Example 3 100g of MCM-22 molecular sieve and 9.02g of gallium nitrate nonahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the support using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-3 was obtained by grinding.
[0029] 100g of ZSM-22 and 50g of SAPO-11 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g of nickel nitrate hexahydrate and 11.04g of ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-3.
[0030] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-3 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. Pellet particles then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-3, which rolled into shape under the action of the atomized binder. The average core layer particle size was controlled to be 2 mm, and the average shell layer thickness was controlled to be 1 mm. The powder was dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-3.
[0031] Example 4 100g of HY molecular sieve and 9.93g of nickel nitrate hexahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-4 was obtained by grinding.
[0032] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-4.
[0033] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-4 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. Pellet particles then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-4, which rolled into shape under the action of the atomized binder. The average core layer particle size was controlled to be 2 mm, and the average shell layer thickness was controlled to be 1 mm. The powder was dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-4.
[0034] Example 5 100g of HY molecular sieve and 9.10g of zinc nitrate hexahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-5 was obtained by grinding.
[0035] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-5.
[0036] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-5 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. Pellet particles then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-5, which rolled into shape under the action of the atomized binder. The average core layer particle size was controlled to be 2 mm, and the average shell layer thickness was controlled to be 1 mm. The powder was dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-5.
[0037] Example 6 100g of HY molecular sieve and 9.02g of gallium nitrate nonahydrate were weighed to prepare an impregnation solution. The active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-6 was obtained by grinding.
[0038] 100g of ZSM-22 and 50g of SAPO-11 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g of nickel nitrate hexahydrate and 11.04g of ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-6.
[0039] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-6 powder was poured into pelletizer A and brought into contact with the atomized binder. The pellets were rolled and formed, and the pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-6. Under the action of the atomized binder, the pellets were rolled and formed, controlling the average particle size of the core layer to be 2 mm and the average thickness of the shell layer to be 1.5 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-6.
[0040] Example 7 100g of ZSM-5 molecular sieve and 9.93g of nickel nitrate hexahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-7 was obtained by grinding.
[0041] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-7.
[0042] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-7 powder was poured into pelletizer A and brought into contact with the atomized binder. The pellets were rolled and formed, and the pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-7. Under the action of the atomized binder, the pellets were rolled and formed, controlling the average particle size of the core layer to be 3 mm and the average thickness of the shell layer to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-7.
[0043] Example 8 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-8.
[0044] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-8.
[0045] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-8 powder was poured into pelletizer A and contacted with the atomized binder, and rolled into shape. The pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-8, which was rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-8.
[0046] Example 9 100g of ZSM-5 molecular sieve and 9.02g of gallium nitrate nonahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the support using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder A-9 was obtained by grinding.
[0047] 100g ZSM-22 and 50g SAPO-11 were dispersed in 1000mL deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g nickel nitrate hexahydrate and 11.04g ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-9.
[0048] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-9 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. Pellet particles then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-9, which rolled into shape under the action of the atomized binder. The average core layer particle size was controlled to be 3 mm, and the average shell layer thickness was controlled to be 1 mm. After drying at 120 ℃ for 6 h and calcining at 500 ℃ for 10 h, core-shell catalyst P-9 was obtained.
[0049] Example 10 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-10.
[0050] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g of nickel nitrate hexahydrate and 11.04g of ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-10.
[0051] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-10 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. The pellets then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-10, which rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-10.
[0052] Example 11 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-11.
[0053] 100g of SAPO-11 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.15g of nickel nitrate hexahydrate and 11.04g of ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-11.
[0054] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-11 powder was poured into pelletizer A and contacted with the atomized binder, and rolled into shape. The pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-11, which was rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-11.
[0055] Example 12 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-12.
[0056] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.25ml of chloroplatinic acid hexahydrate (1g / 25ml platinum concentration) and 11.04g of ammonium molybdate tetrahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-12.
[0057] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-12 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. The pellets then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-12, which rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-12.
[0058] Example 13 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-13.
[0059] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.25ml of 1g / 25ml chloroplatinic acid hexahydrate and 4.43g of tin tetrachloride pentahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-13.
[0060] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-13 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. The pellets then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-13, which rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-13.
[0061] Example 14 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-14.
[0062] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.25ml of 1g / 25ml chloroplatinic acid hexahydrate and 46.17g of chromium nitrate nonahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-14.
[0063] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-14 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. The pellets then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-14, which rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-14.
[0064] Example 15 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-15.
[0065] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then continuously stirred for 20 hours, while simultaneously adding 11.25mL of a palladium chloride hydrochloric acid aqueous solution (1g / 25mL) and 46.17g of chromium nitrate nonahydrate solution under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-15.
[0066] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-15 powder was poured into pelletizer A, where it came into contact with the atomized binder and rolled into shape. The pellets then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-15, which rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-15.
[0067] Example 16 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-16.
[0068] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then continuously stirred for 20 hours, while simultaneously adding 11.25mL of a palladium chloride hydrochloric acid aqueous solution (1g / 25mL) and 8.04g of ammonium metatungstate under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-16.
[0069] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-16 powder was poured into pelletizer A and brought into contact with the atomized binder. The pellets were rolled and formed, and the pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-16. Under the action of the atomized binder, the pellets were rolled and formed, controlling the average core layer particle size to be 3 mm and the average shell layer thickness to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-16.
[0070] Example 17 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder A-17.
[0071] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then continuously stirred for 20 hours, while simultaneously adding 11.25mL of a palladium chloride hydrochloric acid aqueous solution (1g / 25mL) and 4.43g of tin tetrachloride pentahydrate under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder B-17.
[0072] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). A-17 powder was poured into pelletizer A and brought into contact with the atomized binder. The pellets were rolled and formed, and the pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder B-17. Under the action of the atomized binder, the pellets were rolled and formed, controlling the average particle size of the core layer to be 3 mm and the average thickness of the shell layer to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst P-17.
[0073] Comparative Example 1 100g of γ-Al₂O₃ support and 9.10g of zinc nitrate hexahydrate were weighed to prepare an impregnation solution. The active component impregnation solution was impregnated onto the support using an equal-volume impregnation method and left for 16 hours. Then, the support was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder D-1 was obtained by grinding.
[0074] Example 18 The catalyst preparation process is the same as in Example 13, referred to as P-18. The difference between Example 13 and Example 18 is that the raw materials used to evaluate the catalyst performance are different.
[0075] Comparative Example 2 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder D-2 was obtained by grinding.
[0076] Comparative Example 3 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate were weighed to prepare an impregnation solution. The above active component impregnation solution was impregnated onto the carrier using an equal-volume impregnation method and left for 16 hours. Then, it was dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The catalyst core powder C-3 was obtained by grinding.
[0077] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.25ml of chloroplatinic acid hexahydrate (1g / 25ml platinum concentration) and 4.43g of tin tetrachloride pentahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder E-3.
[0078] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). C-3 powder was poured into pelletizer A and contacted with the atomized binder, and rolled into shape. The pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder E-3, which was rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace and reduced at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst D-3.
[0079] Comparative Example 4 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder C-4.
[0080] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution of 11.15g of nickel nitrate hexahydrate and 4.43g of tin tetrachloride pentahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours, then calcined at 550ºC for 4 hours, and finally placed in a tube furnace to obtain catalyst shell powder E-4.
[0081] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). C-4 powder was poured into pelletizer A and contacted with the atomized binder, and rolled into shape. The pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder E-4, which was rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace and reduced at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst D-4.
[0082] Comparative Example 5 100g of ZSM-22, 50g of ZSM-48, and 100g of ZSM-5 molecular sieves were poured into the barrel of an automatic mixer, the equipment was sealed, and the speed was set to 150 r / min for 30 min to ensure that the powders were fully and evenly mixed. After the mixing was completed, the powder mixture was collected and calcined in a muffle furnace to 500 ℃ for 2 h to obtain the mixed carrier.
[0083] A 1g / 25ml solution of zinc nitrate hexahydrate, 4.43g tin tetrachloride pentahydrate, and 11.25ml chloroplatinic acid hexahydrate was prepared. The active component solution was then impregnated onto a carrier using an equal-volume impregnation method and left for 16 hours. The carrier was then dried in an oven at 100ºC for 10 hours and calcined at 550ºC for 6 hours. The resulting catalyst powder, D-5, was obtained by grinding.
[0084] Comparative Example 6 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.25mL of 1g / 25mL chloroplatinic acid hexahydrate and 4.43g of tin tetrachloride pentahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst core powder E-6.
[0085] Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst shell powder C-6.
[0086] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). E-6 powder was poured into pelletizer A and brought into contact with the atomized binder, where it was rolled and formed. The pellets then entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder C-6, which was rolled and formed under the action of the atomized binder. The average particle size of the core layer was controlled to be 2 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst D-6.
[0087] Comparative Example 7 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder C-7.
[0088] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then continuously stirred for 20 hours, while a mixed solution containing 11.25ml of 1g / 25ml chloroplatinic acid hexahydrate and 4.43g of tin tetrachloride pentahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder E-7.
[0089] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). E-7 powder was poured into pelletizer A and contacted with the atomized binder, and rolled into shape. The pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder C-7, which was rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace and reduced at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst D-7.
[0090] Comparative Example 8 Weigh 100g of ZSM-5 molecular sieve and 9.10g of zinc nitrate hexahydrate to prepare an impregnation solution. Impregnate the carrier with the above active component impregnation solution using an equal-volume impregnation method and leave it for 16 hours. Then dry it in an oven at 100ºC for 10 hours and calcine it at 550ºC for 6 hours. Grind it to obtain catalyst core powder C-8.
[0091] 100g of ZSM-22 and 50g of ZSM-48 were dispersed in 1000mL of deionized water to prepare a suspension. The suspension was then stirred continuously for 20 hours, while a mixed solution containing 11.25ml of 1g / 25ml chloroplatinic acid hexahydrate and 4.43g of tin tetrachloride pentahydrate was added under mechanical stirring. After the reaction solution was allowed to stand and cool for 6 hours, it was filtered. The resulting solid was dried at 120ºC for 8 hours and then calcined at 550ºC for 4 hours to finally obtain catalyst shell powder E-8.
[0092] A certain amount of aluminum sol and nitric acid aqueous solution were weighed and prepared into a binder (volume ratio 15:1). E-8 powder was poured into pelletizer A and contacted with the atomized binder, and rolled into shape. The pellets entered pelletizer B from pelletizer A. Pelletizer B contained catalyst shell powder C-8, which was rolled into shape under the action of the atomized binder. The average particle size of the core layer was controlled to be 3 mm, and the average thickness of the shell layer was controlled to be 1.5 mm. The pellets were dried at 120 ℃ for 6 h, calcined at 500 ℃ for 10 h, and finally placed in a tube furnace for reduction at 350 ℃ for 3 h under a hydrogen atmosphere to obtain core-shell catalyst D-8.
[0093] Comparative Example 9 The catalyst preparation process is the same as that of Comparative Example 2, referred to as D-9. The difference between D-9 and Comparative Example 2 is that the raw materials used to evaluate the catalyst performance are different.
[0094] The performance evaluation steps for the catalysts prepared in Examples 1-17 and Comparative Examples 1-8 in the catalytic aromatization reaction of n-hexane to aromatics are as follows: 20 mL of each catalyst sample was taken and packed into a fixed-bed reactor. During the reaction, hydrogen was introduced in gaseous form, and n-hexane or 2-methylpentane was introduced via a plunger pump. The volume hourly space velocity (VHSV) was set to 1.0 h⁻¹. -1 The reaction was carried out at a temperature of 520 °C and a pressure of 0.3 MPa, with a hydrogen to hexane volume ratio of 50:1. The reaction products were then cooled and analyzed by gas chromatography.
[0095] Example 18 and Comparative Example 9 used bio-based mixed light oil with a ratio of C5:C6:C7=10:13:17 as raw materials and carried out catalytic performance tests according to the same steps as described above.
[0096]
[0097] As shown in Table 1, the catalyst prepared according to this invention exhibits superior conversion and aromatic yield compared to typical n-hexane aromatization catalysts, while also demonstrating better stability. For industrial bio-based light oil feedstock, the core-shell catalyst of Example 18 of this invention was compared in parallel with the conventional monofunctional catalyst of Comparative Example 9: Under the same reaction conditions, the bio-based light oil conversion increased from 98.2 wt% to 99.7 wt%, and the aromatic yield increased from 47.5 wt% to 61.3 wt%, representing an increase of 13.8 percentage points in aromatic yield. The core reason lies in the fact that the core-shell structure of this invention achieves spatial functional partitioning: all bio-based raw materials are high-reaction-barrier n-alkanes, which first undergo skeletal isomerization and dehydrogenation through the outer shape-selective isomerizing molecular sieve to generate easily cyclized branched alkanes and olefin intermediates. The intermediates then rapidly diffuse to the core to complete aromatization. In contrast, traditional non-stratified catalysts cannot pre-isolate straight-chain alkanes, resulting in a large number of raw materials undergoing deep cracking side reactions, accelerating carbon deposition, and significantly reducing aromatic selectivity. This fully demonstrates the unexpected technical effect of the core-shell bifunctional catalyst of this invention on bio-based short-chain alkanes.
[0098] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. However, these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions claimed by the present invention.
Claims
1. A catalyst for the hydrogenation aromatization of short-chain alkanes to produce aromatics, characterized in that, The catalyst has a spatially functional core-shell structure, with the core being an aromatization functional catalytic phase and the outer shell uniformly coating the outer surface of the core and being an isomerization-dehydrogenation bifunctional catalytic phase. The raw materials diffuse from the shell to the core, and the isomerization dehydrogenation and cyclization aromatization relay reactions are completed sequentially within a single catalyst particle. The kernel particle size is 0.5–4 mm, the shell thickness is 0.5–4 mm, and the kernel particle size is greater than or equal to the shell thickness.
2. The catalyst for the hydrogenation aromatization of short-chain alkanes to produce aromatics according to claim 1, characterized in that, The core aromatization functional catalytic phase is prepared by supporting an aromatization active metal component on an aromatization molecular sieve support. The aromatization active metal is selected from at least one of Group VIII, IIB, IIIA metal elements, oxides, or metal precursor salts. The aromatization molecular sieve support is selected from at least one of aluminosilicate molecular sieves and pure silica molecular sieves. The shell isomerization-dehydrogenation catalytic phase is prepared by co-loading the isomerization dehydrogenation active component and the promoter onto a shape-selective isomerization molecular sieve support; the shape-selective isomerization molecular sieve support is selected from at least one of ZSM-22, ZSM-48, and SAPO-11; the isomerization dehydrogenation active component is selected from at least one of Group VIII metal elements, oxides, or metal precursor salts; the promoter is selected from at least one of Group VIB and IVA metal oxides or their metal precursor salts.
3. The catalyst for the hydrogenation aromatization of short-chain alkanes to produce aromatics according to claim 2, characterized in that, The core aromatization active metal is at least one of Ni, Zn, and Ga, and the mass fraction of the aromatization active metal in the total mass of the core is 1% to 4% based on the mass of the elemental metal; the metal dispersion of the aromatization active metal on the surface of the aromatization molecular sieve support is greater than 15%. The aromatized molecular sieve support is at least one of HY molecular sieve, MCM-22 molecular sieve, and ZSM-5 molecular sieve.
4. The catalyst for the synthesis of aromatics by the hydrogenation of short-chain alkanes according to claim 2, characterized in that, The shell isomerization dehydrogenation active component is selected from one or more of Ni, Pt, and Pd, and the mass fraction of the isomerization dehydrogenation active component in the total mass of the shell is 0.1% to 2% based on the mass of the metal element. The shell additives are oxides or metal precursors corresponding to Cr, Mo, W, and Sn; the mass fraction of the additives in the total mass of the shell is 1% to 10% based on the mass of the metal oxides.
5. A method for preparing a core-shell catalyst for the hydrogenation aromatization of short-chain alkanes to aromatics as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Preparation of aromatized core particles: The aromatized metal precursor salt solution was impregnated onto the aromatized molecular sieve support by an equal-volume impregnation method for 12–64 h at room temperature; the impregnated product was dried at 100–160 °C for 4–12 h and calcined at 400–600 °C for 4–12 h, and then ground to obtain core powder; a binder was added to the core powder and rolled to form core particles with a particle size of 0.5–4 mm. S2. Preparation of shell-coated powder: Shape-selective isomeric molecular sieves are dispersed in deionized water to prepare a suspension. Under constant temperature of 70-85℃ and stirring speed ≥100rpm, a mixed solution of isomeric dehydrogenation metal precursor and auxiliary precursor is added dropwise. After the addition is completed, stirring is continued for 15-20h. After standing for 4-8h, the solid is filtered and washed. The solid is dried at 100-160℃ for 4-12h and calcined at 400-600℃ for 4-12h, and then ground to obtain shell powder. S3. Rolling and Coating Molding and Post-processing: The core spheres obtained in step S1 and the shell powder obtained in step S2 are fed into a sphere forming device, and the binder is sprayed in by atomization. The spheres are rolled to uniformly coat the surface of the core, and the shell thickness is controlled to be 0.5-4 mm. The coated product is dried at 100-160℃ for 4-12 h and calcined at 400-600℃ for 4-12 h. Finally, it is reduced at 350℃ for 3 h in a hydrogen atmosphere to obtain a core-shell bifunctional catalyst.
6. The preparation method according to claim 5, characterized in that, In step S3, during the ball forming process, the rotation speed of the ball forming equipment is controlled at 20-80 r / min.
7. The preparation method according to claim 5, characterized in that, The binder consists of 20 wt% aluminum sol and 1.0 mol·L⁻¹ -1 The nitric acid aqueous solution is prepared at a volume ratio of 15:
1.
8. The application of a catalyst according to any one of claims 1-4 or a catalyst prepared by the method according to any one of claims 5-7 in the hydrogenation aromatization reaction of short-chain alkanes, characterized in that, Using C3-C8 normal light alkanes as reactants, the conversion is carried out in a hydrogen-containing fixed-bed reactor. The reactants first undergo isomerization and dehydrogenation reactions in the catalyst shell to generate isoalkanes and low-carbon olefin intermediates. The intermediates diffuse inward to the catalyst core to undergo cyclization and aromatization reactions to generate aromatics.
9. The application according to claim 8, characterized in that, The reaction conditions were: reaction pressure 0.1~1 MPa, reaction temperature 480~550℃, and volume hourly space velocity 0.5~2 h⁻¹. -1 The volume ratio of hydrogen to raw materials is 10:1 to 200:
1.
10. The application according to claim 9, characterized in that, The short-chain alkanes are selected from one or more mixtures of C3-C8 light alkanes.